Identity and Self-Consiousness: the Links Between Psychology and Sociology - Legkauskas, Visvaldas (Sociologija. Mintis ir veiksmas, 2000)
The problematique of identity is one of the most important in the social science at the end of twentieth century. Lithuania is not an exception. However, there are only a few attempts in Lithuania to discuss the relationship between sociological and psychological analysis of identity. The concept of identity is is a dynamic one: it does not allow a clear distinction between the self and the society; and yet it does not provide an image of their identity. Because of this the sociological and the psychological analyses are interrelated. The aim of the article is to discuss the interrelation metatheoretically and to develop the Lithuanian-sociological vocabulary of the problematique.